Faith in verse: biblical presence in contemporary Anglo-American poetry - Reisner, Philipp (New directions in religion and literature, 2026)
Klappentext: "Examining the profound influence of biblical themes on contemporary poetry written in English, this book explores the work of Brooks Haxton, Suji Kwock Kim, Kevin Hart, and Li-Young Lee. Going beyond a mere examination of literary works, it considers how the presence of biblical references shapes and transforms contemporary Anglo-American poetry in unique and compelling ways"-- Provided by publisher